2014
DOI: 10.1210/jc.2013-2963
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Fibroblast Growth Factor 23, Parathyroid Hormone, 25-Hydroxyvitamin D3, and Risk of Heart Failure: A Prospective, Case-Cohort Study

Abstract: Our findings provide epidemiological evidence for a positive relationship between FGF23 and risk of HF. The role of PTH in the development of HF remains unclear, in particular in obese individuals, until further confirmation in other studies. 25(OH)D3 was not related to HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 37 publications
2
40
1
1
Order By: Relevance
“…41 The Physicians' Health Study (mean age, 58.6 years) and the European Prospective Investigation into Cancer and Nutrition-Potsdam study also showed no association between plasma vitamin D-binding protein or 25(OH)D3 with risk of HF. 22,26 The finding that 25OHD deficiency is not associated with HF in older adults is consistent with the findings from several cross-sectional population studies that 25OHD is not associated with any biochemical conduction or echocardiographic outcomes. 16,17 …”
Section: Vitamin D and Incident Hfsupporting
confidence: 88%
See 3 more Smart Citations
“…41 The Physicians' Health Study (mean age, 58.6 years) and the European Prospective Investigation into Cancer and Nutrition-Potsdam study also showed no association between plasma vitamin D-binding protein or 25(OH)D3 with risk of HF. 22,26 The finding that 25OHD deficiency is not associated with HF in older adults is consistent with the findings from several cross-sectional population studies that 25OHD is not associated with any biochemical conduction or echocardiographic outcomes. 16,17 …”
Section: Vitamin D and Incident Hfsupporting
confidence: 88%
“…Two studies have shown elevated PTH to be associated with HF independent of known risk factors, including hypertension and renal dysfunction, 20,21 whereas 1 study suggested the association to be present in obese subjects only. 22 We have shown elevated PTH (>55.6 pg/mL) to be associated with increased HF risk in both men with and without established CVD (MI/stroke). Although the association appeared to be stronger in obese men, there was no evidence of an interaction.…”
Section: Pth and Incident Hfmentioning
confidence: 84%
See 2 more Smart Citations
“…43 Single nucleotide polymorphisms (SNPs) in FGF-23 have been identified as potential risk factors for cardiac abnormalities in Kawasaki disease, 44 and the serum levels of FGF-23 have been recognized as biomarkers for cardiovascular failure. 45 FGF-23 had also been linked to greater risks of left ventricular hypertrophy in patients with CKD. 46 However, no conclusion has been reached whether this effect is via α-klotho independent pathways or indirectly due to the renal effects of FGF-23.…”
Section: Heartmentioning
confidence: 99%